Colorectal large‐cell neuroendocrine carcinoma with lymphoid stroma: further evidence confirming a unique subtype associated with MLH1/PMS2 loss, BRAF mutation, Epstein–Barr virus negativity, and the possibility of a better prognosis. Issue 2 (2nd July 2019) - Chetty, Runjan; Capo‐Chichi, Jose‐Mario; Serra, Stefano
Abstract : Aims: Pure large‐cell neuroendocrine carcinoma (LCNEC) is an uncommon but well‐recognised primary tumour of the colorectum. It is characterised by large cells organised in a discernible neuroendocrine pattern with >20 mitoses per 10 high‐power fields (HPFs), and/or a Ki67 index of >20%, and coagulative tumour necrosis is invariably present. These features are supplemented by positivity for neuroendocrine immunohistochemical markers. The aim of this study was to highlight three primary LCNECs of the colorectum. Methods and results: All three patients were elderly females, aged 79, 85 and 89 years, who presented with ascending colon (two) tumours and a rectal tumour. All three tumours were large, ulcerated, polypoid masses (85, 76 and 55 mm; average size 72 mm) and were pT3N2. Histologically, the tumours were composed of packets and nests of cells with rosettes; other areas were in sheets composed of large cells. The mitotic counts were 23/10 HPFs, 27/10 HPFs and 24/10 HPFs, respectively. There was no mucosal dysplasia, precursor adenoma or associated adenocarcinoma component. All cases contained mainly peritumoral lymphoid aggregates, with smaller numbers of intratumoral lymphocytes. Synaptophysin, chromogranin (less intensely) and epithelial markers were expressed in all cases in the majority of the tumour cells. The Ki67 proliferative indices were 95%, 100%, and 80%, respectively. Two patients survived for 48 and 72 months, whereas the third is alive after 12 months without evidence of recurrence. Conclusions: These unusual primary colorectal LCNECs with an accompanying lymphoid component are characterised by loss of MLH1/PMS2, BRAF mutation, microsatellite instability, and Epstein–Barr virus negativity. The patients also have better overall survival than those with LCNECs lacking an accompanying lymphoid component.